PENGARUH RETURN ON EQUITY, CURRENT RATIO,DEBT TO EQUITY RATIO, TOTAL ASSETS TURN OVER DAN EARNING PER SHARE TERHADAP RETURN SAHAM - Ananto, Niel (JBE (Journal of Business and Economics); Volume 13 No.1, 2014 JBE UNKLAB, 2014)
This study aims to test whether the Return On Equity (ROE), the Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO) AND Earning Per Share (EPS) have an influence on stock returns at property company real estate listed on the Indonesia Stock Exchange. The variables of this study are: the dependent variable (Stock Return) and the independent variables consict of (Return On Equity (ROE), the Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO) and Earning Per Share (EPS) ). The sample in this study are the financial statements of 16 companies of real estate properties listed 2010-2012 in Indonesia Stock Exchange. Sampling techniques in this study by using simple random sampling, where each element of the population has an equal chance to become the sample. The data were collcted from Indonesia Stock Exchange and analyzed by correlation technique and multiple regression method. The result is simultaneously Return On Equity (ROE), the Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turn Over (TATO) and Earning Per Share (EPS) has a significant influence on stock return. When in only partial test Current Ratio (CR) and Earning Per Share (EPS) which has significant influence on stock return.